XXVI International Symposium on Biomechanics in Sports (2008)
ISBS 2008 will be held from July 14(Monday) to July 18(Friday), 2008 at Seoul National University, Seoul, Korea. The Scientific Program of the conference will contain keynote lectures(7), oral presentations (up to 150), poster presentations, workshops and Applied Programs (4). General Topic of the Conference: Biomechanics for performance enhancement